Ag10Ti28‐Oxo Cluster Containing Single‐Atom Silver Sites: Atomic Structure and Synergistic Electronic Properties - Chen, Shuai; Chen, Zhe‐Ning; Fang, Wei‐Hui; Zhuang, Wei; Zhang, Lei; Zhang, Jian (Angewandte Chemie International Edition, 2019)
Supported single‐atom catalysts have been emerging as promising materials in a variety of energy catalysis applications. However, studying the role of metal–support interactions at the molecular level remains a major challenge, primarily due to the lack of precise atomic structures. In this work, by replacing the frequently used TiO2 support with its molecular analogue, titanium‐oxo cluster (TOC), we successfully produced a new kind of Ti‐O material doped with single silver sites. The as‐obtained Ag10Ti28 cluster, containing four exposed and six embedded Ag sites, is the largest noble‐metal‐doped Ti‐O cluster reported to date. Density functional theory (DFT) calculations show that the Ag10Ti28 core exhibits properties distinct from those of metallic Ag‐based materials. This Ti‐O material doped with single Ag sites presents a high ϵd and moderate CO binding capacity comparable to that of metallic Cu‐based catalysts, suggesting that it might display different catalytic performance from the common Ag‐based catalysts, for example, for CO2 reduction. These results prove that the synergism of active surface metal atoms and the Ti‐O cluster support result in unique physical properties, which might open a new direction for single‐atom‐included catalysts. Advantageous conjunction: The largest noble‐metal‐doped Ti‐O cluster, Ag10Ti28‐oxo, contains single silver sites. The synergism between the active surface metal atom and the Ti‐O cluster support produces unique electronic properties that are distinct from those of metallic Ag‐based materials.